A taxonomic view of cloud computing services. (2015) - Forti?, Teodor-Florin; Munteanu, Victor Ion; Negru, Viorel
With the massive adoption of cloud computing, a growing number of small and medium enterprises (SMEs) now have the opportunity, together with the immediate goal of reducing cost, to effectively expose their services or group themselves into clusters or virtual enterprises in order to build and expose customised offerings. Different requirements, ranging from interoperability and portability, provisioning and reconfiguration, security and privacy, or monitoring and auditing, can all be controlled through the lifecycle support of cloud services and grouped under the umbrella of different virtual enterprises. A semantic support is essential to enable such an entity, and to foster collaboration among different virtual enterprises by providing specific mechanisms by which the construction of complex services from elementary building blocks can be made possible. At the same time it actively supports tasks like automation of cloud resource usage, efficient monitoring and scaling of cloud services, either individually or based on specific dependencies, or replacement and termination of services when the initial offers are no longer available.